Analysis of Factors Affecting Local Original Income (PAD) Pakpak Bharat - Renauli, Benni Berutu (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the influence of DAU (Block Grant), DAK (Special Grant), DBH (Profit Sharing Fund), BM (Capital Expenditure), and Population on PAD (Regional Generate Revenue) of Pakpak Bharat Regency. This is a descriptive quantitative research which describes its findings through explanation based on figures. The research population was 72 data obtained from budget realization report of Pakpak Bharat Regency for 6 (six) years from 2011 until 2016. The samples were taken by employing saturated sampling technique in which the whole population was taken as the samples. The data were analyzed by using multiple linear regression method. The results showed that Simultaneously, DAU, DAK, DBH, BM, and population influenced PAD of Pakpak Bharat Regency. Partially DAU and DAK influenced PAD of Pakpak Bharat Regency whereas DBH, BM, and Population did not have any influence